Breast Cancer Surgery, History and Current State: a Literature Review - E. P. Kashirina; R. N. Komarov; D. V. Vychuzhanin (Креативная хирургия и онкология, 2021)
Breasts symbolise femininity, sexuality and motherhood. The breast size and shape affect the woman’s self-esteem and social activity. Surgical treatment of malignant breast diseases concerns the medical, psychological, social and sexual aspects of life. Surgery for breast cancer dawns back to 1,600 B.C., with a milestone operation of radical mastectomy proposed in 1891–1894 by W. Halsted and W. Meyer and modified by D. Patey and W. Dyson in 1948. Tissue preservation has shaped a trend towards improving the technique. Since the 1990s, the modified J. Madden’s operation has become the treatment standard in breast cancer, irregardless of stage. The improvement of mass first-visit check-up advanced early diagnosis of initial breast tumourisation, which also influenced the choice of surgical tactics. U. Veronesi proposed a variant of organ-preserving surgery in 1970–80s involving three-level axillary lymph node dissection quadrantectomy, followed by radiotherapy. This combination facilitated aesthetic results at no compromise of radicality of the treatment. The need to observe radicality and sustain aesthetics contributed to the integration of plastic surgery into oncological cure and emergence of reconstructive and plastic breast surgery. The field has entered new cycle. Oncoplastic surgery is recognised safe, improves aesthetics and gives a salutary impact on psychological and social adjustment. Manifold surgical options in breast cancer coexist and develop towards maximal tissue preservation.